Pregnancy outcomes in connective tissue diseases: a 30-year study of 465 cases from a single-center Spanish registry with insights on hydroxychloroquine use - Cristiana Sieiro Santos; José Ordás Martínez; Clara Moriano Morales; Carolina Alvarez Castro; Elvira Díez Álvarez (ARP Rheumatology)
Introduction: Pregnancy in women with connective tissue diseases (CTDs), including systemic lupus erythematosus (SLE), systemic sclerosis (SSc), primary Sjögren’s syndrome (pSS), and undifferentiated connective tissue disease (UCTD), poses significant risks for adverse outcomes. Evaluating these risks and outcomes is essential to improve maternal and fetal health. Objectives: This study aimed to assess pregnancy outcomes in patients with CTDs, identify factors associated with adverse outcomes, and evaluate the protective effects of hydroxychloroquine (HCQ) treatment. Methods: A study covering the period from 1990 to 2022 was conducted. Data were collected from medical records of childbearing-age women with SLE, SSc, pSS, and UCTD who were under care at our clinic. Obstetric, maternal, and fetal outcomes were analyzed across different diagnoses. Statistical analyses were performed to identify associations between disease activity, treatments, and pregnancy outcomes. Results: A total of 295 patients (125 with SLE, 50 with SSc, 80 with pSS, and 40 with UCTD) and 465 pregnancies were included. The mean age at first pregnancy was 29.1±9.1 years. Pregnancy loss occurred in 21% of cases, while 77% resulted in live births. Adverse outcomes included preterm delivery (8%), postpartum hemorrhage (6%), and preeclampsia (5%). SLE diagnosis (OR 1.5, 95% CI [1.1–4.8], p = 0.03), double/triple antiphospholipid antibody (APL) positivity (OR 2.3, 95% CI [1.1–3.9], p = 0.04), and active disease (OR 3.4, 95% CI [1.8–5.2], p = 0.004) were identified as risk factors for adverse pregnancy outcomes. HCQ treatment demonstrated a protective effect (OR 0.34, 95% CI [0.05–0.72], p = 0.0004). Conclusion: Two-thirds of pregnancies in women with CTDs resulted in live births, though SLE was associated with significantly higher risks. Active disease during pregnancy emerged as a major risk factor. Importantly, the use of HCQ was associated with a notable reduction in these risks, underscoring its protective role in improving pregnancy outcomes. These findings highlight the critical importance of preconception counseling, careful disease management, and the proactive use of HCQ to minimize complications and optimize outcomes in pregnancies complicated by CTDs.